2022
DOI: 10.3390/diagnostics12102312
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Cognitive Training in Older Adults with Different APOE Genotypes and COVID-19 History: A 1-Year Follow-Up Cohort Study

Abstract: (1) Background: Older people suffer from cognitive decline; several risk factors contribute to greater cognitive decline. We used acquired (COVID-19 infection) and non-modifiable (presence of APOE rs429358 and rs7412 polymorphisms) factors to study the progression of subjective cognitive impairment while observing patients for one year. Cognitive training was used as a protective factor. (2) Methods: Two groups of subjects over the age of 65 participated in the study: group with subjective cognitive decline re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Multidisciplinary training includes lifestyle changes, as it has been shown that this type of training is the most effective [44]. We have previously demonstrated a positive effect of cognitive training on cognitive functioning in MCI patients [50], and it is expected that it may produce an effect on some physiological and biochemical indicators of cognitive decline. Interestingly, cognitive training affected only cognitive test scores but did not influence depression or anxiety scores.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Multidisciplinary training includes lifestyle changes, as it has been shown that this type of training is the most effective [44]. We have previously demonstrated a positive effect of cognitive training on cognitive functioning in MCI patients [50], and it is expected that it may produce an effect on some physiological and biochemical indicators of cognitive decline. Interestingly, cognitive training affected only cognitive test scores but did not influence depression or anxiety scores.…”
Section: Discussionmentioning
confidence: 97%
“…Cognitive training is a rehabilitation program conducted in our hospital [57,58]. According to previous studies, such rehabilitation reduces the severity of cognitive manifestations and their progressive deterioration [50,57,58]. The goal of our neurocognitive rehabilitation strategy is to improve the quality of life of elderly citizens, increase the period of active longevity, restore cognitive deficits and prevent dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al evaluated 142 patients with COVID-19 and found that those with APOE E4 had elevated inflammatory factors [8]. In another study, Zorkina et al did not find any influence of the baseline serological status for COVID-19 and the APOE gene polymorphism on cognitive rehabilitation in a sample of individuals over 65 years old measured through changes in Mini-Mental State Examination (MMSE) scores [9]. This association is significant, as the same allele confers a higher risk of sporadic Alzheimer's disease (AD) [10].…”
Section: Introductionmentioning
confidence: 99%